ENDOVASCULAR REVASCULARIZATION METHODS IN THE TREATMENT OF ACUTE LOWER LIMB ISCHEMIA: THE CURRENT STATE OF KNOWLEDGE - A.D. GAIBOV; O. NEMATZODA; D.D. SULTANOV; K.A. ABDUSAMADOV; SH.A. SHOKHSAVORBEKOV; A.K. BARATOV (Паёми Сино)
Objective: To determine the role and significance of endovascular revascularization methods in treating acute lower limb ischemia (ALLI) from the perspective of modern literature.